The Role of Aspiration Flows in Saving Time to Study the Operative Situation in Emergency Situations - S. T., Ruziev (European Journal of Life Safety and Stability (2660-9630), 2022)
The article found that the time allotted for the localization of the consequences of an emergency (fire) can be divided into three components tф.в.=t1+t2+t3 . As a result tф.в.=t1+t2+t3 where tф.в. - the time at our disposal, ie the time remaining until the point "Ch"; ti is the time spent for each stage (i = 1,…, 3) to prove based on the results obtained.